2011
DOI: 10.1002/uog.8950
|View full text |Cite
|
Sign up to set email alerts
|

A new method for analysis of non‐pregnant uterine peristalsis using transvaginal ultrasound

Abstract: Objectives To develop an objective method for analysis of uterine peristalsis using transvaginal sonography (TVS). Methods

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 15 publications
3
20
0
Order By: Relevance
“…The tongue kinematics was analyzed from in vivo submental ultrasound video clips. The computational methods were similar to those used in our previous studies where we converted video clips of medical images into time-dependent biological data that can be analyzed in the time-frequencyspace domains for the enhancement of physiological knowledge (Elad et al, 2014;Eytan et al, 1999;Gora et al, 2016Gora et al, , 2018Meirzon et al, 2011;Zhang et al, 2019). The experimental and objective computational approach to explore tongue kinematics during infant feeding or adult swallowing is schematically shown in the flow chart depicted in Figure 1.…”
Section: Methodsmentioning
confidence: 99%
“…The tongue kinematics was analyzed from in vivo submental ultrasound video clips. The computational methods were similar to those used in our previous studies where we converted video clips of medical images into time-dependent biological data that can be analyzed in the time-frequencyspace domains for the enhancement of physiological knowledge (Elad et al, 2014;Eytan et al, 1999;Gora et al, 2016Gora et al, , 2018Meirzon et al, 2011;Zhang et al, 2019). The experimental and objective computational approach to explore tongue kinematics during infant feeding or adult swallowing is schematically shown in the flow chart depicted in Figure 1.…”
Section: Methodsmentioning
confidence: 99%
“…Differences in thickness among uterine segments can also represent other patterns of uterine activity as peristalsis (37, 38, 51), which has been previously associated with placental detachment (52). Uterine peristalsis has been described using ultrasound and MRI techniques in non-pregnant women (53-65) as inherent, subtle, and rhythmic movements in the endometrium and the innermost zone of the myometrium (54) that is hormonally stimulated (56, 57, 66, 67). In women with endometriosis uncoordinated and arrhythmic uterine contractions have been described as “hyperperistalsis or dysperistalsis” (67, 68).…”
Section: Discussionmentioning
confidence: 99%
“…The objective computerized analysis of TVUS video clips revealed motility of the FEI with amplitudes of 0.01–0.19 mm and frequencies of 0.005–0.09 Hz during days 10–16 . More recently, it has been shown that the EMI motility has amplitudes of 0.6–2.0 mm and frequencies of 0.029–0.087 Hz …”
Section: Uterine Peristalsismentioning
confidence: 99%
“…Contractility of smooth muscle depends on levels of hormones, and accordingly, their characteristics vary during the menstrual cycle. Many studies of human uterine peristalsis revealed cervix‐to‐fundus directed contractions at rates of 1–5 contraction/min during the proliferative and secretory phases, while during the menstrual phase the direction is reversed with smaller rates of 0.5–2.5 contraction/min and larger amplitudes …”
Section: Uterine Peristalsismentioning
confidence: 99%
See 1 more Smart Citation